Paediatric screening for hypercholesterolaemia in Europe. Issue 3 (26th September 2011) - Kusters, D M; de Beaufort, C; Widhalm, K; Guardamagna, O; Bratina, N; Ose, L; Wiegman, A
Abstract : Different screening strategies are currently recommended to identify children with (familial) hypercholesterolaemia in order to initiate early lipid management. However, these strategies are characterised to date by low adherence by the medical community and limited compliance by parents and children. In a literature review, the authors assess which children should undergo screening and which children are in effect identified through the currently recommended strategies. Furthermore, the authors discuss the different screening tools and strategies currently used in Europe and what is known about the negative aspects of screening. The authors conclude that currently recommended selective screening strategies, which are mainly based on family history, lack precision and that a large percentage of affected children who are at increased risk of future coronary artery disease are not being identified. The authors propose universal screening of children between 1 and 9 years of age, a strategy likely to be most effective in terms of sensitivity and specificity for the identification of children with familial hypercholesterolaemia. However, this concept has yet to be proven in clinical practice.